Group I mGluR-dependent depotentiation in the lateral amygdala does not require the removal of calcium-permeable AMPA receptors - Park, Kyungjoon; Song, Sukwoon; Hong, Ingie; Song, Beomjong; Kim, Jeongyeon; Park, Sungmo; Lee, Junuk; Song, Sangho; An, Bobae; Kim, Jihye; Lee, C. Justin; Shin, Ki Soon; et al. (Frontiers in Behavioral Neuroscience, 2014)
There is conflicting evidence regarding whether calcium-permeable receptors are removed during group I mGluR-mediated synaptic depression. In support of this hypothesis, AMPAR rectification, a correlative index of the synaptic expression of GluA2-lacking calcium–permeable AMPARs (CP-AMPARs), is known to decrease after the induction of several types of group I mGluR-mediated long-term depression (LTD), suggesting that a significant proportion of synaptic CP-AMPARs is removed during synaptic depression. We have previously demonstrated that fear conditioning-induced synaptic potentiation in the lateral amygdala is reversed by group 1 mGluR-mediated depotentiation. Here, we examined whether CP-AMPARs are removed by mGluR1-mediated depotentiation of fear conditioning-induced synaptic potentiation. The synaptic expression of CP-AMPARs was negligible before, increased significantly 12 hrs after, and returned to baseline 48 hrs after fear conditioning, as evidenced by the changes in the sensitivity of lateral amygdala synaptic responses to NASPM. Importantly, the sensitivity to NASPM was not altered after induction of depotentiation. Our findings, together with previous results, suggest that the removal of CP-AMPARs is not required for the depotentiation of fear conditioning-induced synaptic potentiation at lateral amygdala synapses.